PEMBERDAYAAN PEREMPUAN DALAM PARTAI POLITIK DI PROVINSI BALI (STUDI PADA PARTAI PDIP, DEMOKRAT DAN PSI) - Oktapiani, Komang Eva; Bandiyah, Bandiyah; Mahaswari Jaya Mertha, A.A Sagung Mirah (Jurnal Nawala Politika, 2020)
ABSTRACT The preparation of this research aims to provide overview of women empowerment in PDIP, Demokrat and PSI parties in Bali Province. This research uses Liberal Feminism theory from David Marsh and Gerry Stoker which declare there are struggles for women’s right in various aspects and one those is political aspect. The method used is descriptive qualitative that explains the incident and phenomenon that occurs so get information that is in accordance with the fact and the real situation as well. The findings of this study is showing that the party has implemented several strategies to empowering women, but the implementation is not running optimally because the domination still strong and the public trust in men, it needs an understanding that women can also fight for the same rights. Keywords: Women’s Empowerment, Political Parties, Bali Province